Pengaruh Model Pembelajaran Quantum Teaching terhadap Hasil Belajar Siswa SMA Pada Materi Laju Reaksi - Harni Anhar S. Ambololo; Weny J.A. Musa; Erga Kurniawati; Mangara Sihaloho; Hendri Iyabu (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
This study aims to identify differences in student learning outcomes between those who receive learning using the Quantum Teaching model and those who receive conventional learning on the material of reaction rates at SMA Negeri 1 Tapa. This study is a quantitative study that applies a quasi-experimental method through a control group design with pretest and posttest. The results of the study indicate that after the application of the Quantum Teaching learning model in the experimental class and the use of the conventional learning model in the control class, there was an increase in student learning outcomes. The average pretest score of the experimental class was 34.37 and the posttest score reached 77.31, while for the control class, the average pretest score was 39 and the posttest score was 58.21. It can be seen that both groups of classes showed significant progress , which can be seen from the higher scores in the experimental group when compared to the control group . The hypothesis was tested through a mean test ( t- test ). The results of the Paired Sample t-test in the experimental group showed a significant difference between the pretest and posttest results, with a significance value of 0.000 , which is much lower than the limit of α = 0.05. This study shows that learning using the Quantum Teaching model has a positive impact on improving students' conceptual understanding.